Modulation of the catalytic activity of porphyrins by lipid-and surfactant-containing nanostructures - Nantes,Iseli L (2011)
The structural factors modulating porphyrin activity encompass pyrrole and equatorial ligands, as well as the central metal and the number and structure of their axial ligands. Of equal importance is the microenvironment provided by apoproteins, solvents and membranes. Porphyrins are often used to construct supramolecular structures with different applications. The modulation of activity of the porphyrins has been frequently achieved by mimicking nature, i.e., by the provision of different microenvironments for these molecules. The association of porphyrins to surfactant- and lipid-containing nanostructures has changed the activity of these compounds to mimic different enzymes such as SOD, cytochrome P450, peroxidases and others. In determined conditions, the reactive forms of the porphyrins are high-valence states of oxo-metal-πcations and oxo-metal produced by the reaction with peroxides and peracids. The modulation of porphyrin activity by surfactant- and lipid-containing nanostructures has also been achieved for hemeproteins, as the lipid nanostructures affect the conformation of proteins.